Effects of remimazolam on hemodynamics in children with congenital heart disease undergoing cardiac catheterization - Li, Hongyun; Song, Zhaomeng; Jiang, Xunwei; Liu, Wei; Jiang, Yan; Wei, Rong (Frontiers in Pharmacology, 2025)
IntroductionMaintaining hemodynamic stability during anesthesia is crucial for patients with congenital heart disease. Remimazolam, a novel benzodiazepine, offers advantages, such as rapid onset, quick recovery, stable hemodynamics, and mild respiratory depression. We aimed to assess the effects of a single intravenous dose of remimazolam on hemodynamics in children with congenital heart disease.MethodsThis self-controlled before-and-after study enrolled 40 children undergoing elective cardiac catheterization and transcatheter interventional closure at Shanghai Children’s Hospital between June and September 2024. No special preoperative medications were administered. After entering the operating room, noninvasive hemodynamic parameters, such as heart rate (HR), mean arterial pressure (MAP), oxygen saturation (SPO2), cardiac output (CO), and cardiac index (CI) were monitored. During the cardiac catheterization procedure, invasive hemodynamic parameters—including superior vena cava pressure (SVCP), right atrial pressure (RAP), right ventricular pressure (RVP), and pulmonary artery pressure (PAP)—were measured according to surgical requirements. Subsequently, remimazolam (0.3 mg/kg) was administered intravenously, and the same parameters were remeasured 3 min later. The impact of remimazolam on hemodynamics in children with CHD was evaluated by comparing the changes in these indicators before and after drug administration.ResultsFive patients were excluded due to incomplete data, leaving 35 for analysis (sex, 11 male, 24 female; median age, 6.67 [interquartile range: 4–11.5 years]). Following intravenous administration of remimazolam, all non-invasive hemodynamic parameters remained stable, showing no statistically significant differences before versus after medication: HR [(104.31 ± 20.27) vs. (104.91 ± 19.76) bpm, P = 0.485], MAP [61 (58, 65) vs. 61 (57, 66) mmHg, P = 0.313], CO [3.2 (2.34, 3.5) vs. 3 (2.41, 3.7) L/min, P = 0.133], and CI [3.3 (3, 3.6) vs. 3.3 (3, 3.71) L/min/m2, P = 0.292]. Similarly, no statistically significant differences were observed in right heart system pressures before and after administration: mRAP [8 (6, 10) vs. 8.5 (6.75, 10.25) mmHg, P = 0.064] and mPAP [15.5 (14, 19) vs. 16 (14, 19.5) mmHg, P = 0.517]. No adverse reactions such as bradycardia, hypotension, or hypertension were observed after intravenous injection of remimazolam.ConclusionDuring sevoflurane-maintained anesthesia, co-administration of remimazolam provides good hemodynamic stability for children with left-to-right shunt congenital heart disease undergoing cardiac catheterization.